Nonexponential dielectric relaxation dynamics in supercooled liquid and glassy states of isoamyl bromide and 2-methylpentane mixtures - VIJ, JAGDISH KUMAR (American Institute of Physics, 2001)
The dielectric spectra of mixtures of the polar solute isoamyl bromide in 2-methylpentane have been investigated in the frequency range 1 mHz to 1 MHz and in the temperature range approaching the glass transition temperature. The results obtained from the spectra are compared with those obtained recently [J. Chem. Phys. 111, 10979 (1999)] on pure isoamyl bromide. It is found that on increasing dilution with the nonpolar solvent, the width of the curves of the dielectric spectra increase significantly, and this is reflected in the increase in the nonexponential nature of the relaxation dynamics. This is found to be a consequence of the decrease in the cooperativity of the relaxation dynamics and or an increase in the heterogeneity of the solution. The data are found to fit the Havriliak?Negami equation extremely well. The data at low and high frequencies also fits the "universal law," since the latter is a low and high frequencies limiting case of the Havriliak?Negami equation. The scaling parameters of this law are calculated for the 25 mol % solution of isoamyl bromide in 2-methylpentane, and these are shown to experimentally relate to the H?N parameters. The stretched exponential parameter, , is estimated as a function of the temperature and is shown to follow the equation a(T?T0). Vogel?Fulcher?Tammann equation fits the data of the relaxation peak frequency as a function of the inverse of absolute temperature for the various mixtures quite well, this being possibly a consequence of the temperature dependence of the stretched exponential parameter. The predictions from the mode coupling theory and those by Bertrand and Souletie are verified with the exception that the exponent is found to be much greater than predicted by these theories. The relative predominance of the Johari?Goldstein process in isoamyl bromide increases initially with dilution with 2-methylpentane and then disappears as the number density of the independent relaxors increases with further dilution.
PUBLISHED
Keywords: Condensed matter physics; dielectric relaxation